Hematoma subdural dorsal espontâneo. - Bruno Alpoim; Maria Rodrigues; Pedro Silva; Bruno Carvalho; Paulo Pereira; Rui Vaz (Acta Médica Portuguesa, 2011)
Spontaneous spinal subdural hematomas are rare and may be caused by vascular malformations or bleeding disorders. The diagnosis is based on the conjunction of clinical examination with imaging studies, being MRI the gold standard in detection and surgical planning. The authors report the case of a patient on anticoagulant therapy in the context of atrial fibrillation and mechanical prosthetic mitral and tricuspid valves, presenting with sudden onset of dorsal pain radiated to both lower limbs, paresthesias and progressive paraparesis. The impossibility to perform MRI (because the mechanical valve prostheses) hindered the diagnosis of acute spontaneous subdural hematoma. After reversal of the anticoagulation and surgical treatment, clinical course was favorable with neurological recovery.